Expression of Lithuanian Photographic Art in the Context of Cultural Sovietisation (1958–1970) - Matulytė, Margarita (Genocidas ir rezistencija, 2005)
The article analyses tendencies in photographic art and the ideology which formed and ruled them in the post-Stalinist period. The chronological range (1958–1970) chosen for consideration marks the second stage of Soviet Lithuanian photography the beginning of collective public work. The mode of realistic depiction was modified and relatively liberalized in the years of the "Thaw" but still preserved the original ideology which enabled the strengthening of the Soviet regime. It was acknowledged that photography suffered a decline during the years of Joseph Stalin's rule. There was open criticism of the requirements which prevailed during that period of photographic art genres and composition, yet the search for new forms of expression was restrained. More attention was paid to the reporting genre as presenting greater opportunities for innovation and more suited to the realistic depiction of socialistic society. The propaganda of social humanism engrained in photographic art was based on the complete identification of the individual with the interests of the system.
Keywords: art; culture; photography; Soviet culture; cenzorship; communist ideology